Luxury vs. Popular: analysis of Karl Lagerfeld for Riachuelo Collection’s (ModaPalavra e-periódico, 2019)
The article presents a brief contextualization of the Brazilian contemporary scenario and its peculiarities that reflect the market strategies, to attend the user who seeks the individualization through the means of products. In this context, it is approached as fast-fashionnetworks that establish partnerships with luxury brands, to facilitate access to high fashion information, for those who can not have access to an item of this category. More specifically, the focus of this article is a partnership between Karl Lagerfeld and Riachuelo, who in 2016 launched a fashion collection with elements reminiscent of the stylist's personal style and the Chanel brand. The objective is to understand the signs of the creator and the possible meanings generated by the individuals when acquiring the products. For this, a qualitative approach was used, a bibliographical research and an analysis to support a three-look analysis of the collection. The parameters that were cranes were the objective / subjective wealth levels of Bomfim (1997). As a result, personal signs have been created in relation to the creator and the universe of luxury that surrounds them.
Keywords: brazilian contemporary scenario; fashion products; Karl Lagerfeld for Riachuelo